The Impact of Social Media and Lifestyle on the Decision to Become a Customer at PT. Bank Syariah Indonesia KCP Tomang Elok Medan - Putra, Romi Adi; Pradesyah, Riyan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to look at the influence of social media and lifestyle on the decision to become a customer of Bank Syariah Indonesia (BSI). This is because the market share of Islamic banks in Indonesia is experiencing a fairly slow increase, while the number of Islamic banks in Indonesia from year to year continues to increase. So, it requires testing variables that can increase customer decisions in making transactions at Islamic banks. The approach to completing this research, using quantitative methods, is to test variables that are considered important in decision-making. Then the analysis tool used is SmartPLS. The population in this study was customers at BSI Tomang Elok, then drew samples using the Slovin formula, and obtained samples of 94 customers. The results obtained that, there is an influence of people’s lifestyles on the decision to become a customer, then there is no influence of social media on decision making to become an Indonesian Islamic bank customer. The model obtained in this study is ????1 = 0.627????1 + 3.396????2 + ????.